Analysis of Availability and Need for Parking Space at Top Mode Stores Jl. Perintis Kemerdekaan - Anugrah Sarungngu Timang; Rais Rachman; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2022)
Parking needs are one of the problems that are inseparable, especially in shopping areas that are important places for consumers in the area, especially private vehicle users, shops must provide parking facilities with the aim that parking characteristics in the shopping area can be overcome, This research aims to determine needs and availability of parking space also the characteristics of parking in Top Mode stores. The method used is the collection of primary data in the field in the form of vehicles coming and exiting for analysis of capacity, volume, accumulation, duration, and parking index, According to planning guidelines and operation of the 1998 ministry of transportation general park facility. The results of this study are the maximum parking volume for cars as many as 18 vehicles at 14:30-14:45 WITA and for motorcycles as many as 72 vehicles at 17:15-17:30. Maximum parking accumulation for cars as much as 66 plots at 17.00-17.15 WITA and for motorcycles as much as 243 plots of parking at 17:30-17:45 WITA Comparing with parking guidelines, some parameters have not met the specifications, much as, volume, accumulation, parking space unit, parking needs, and parking index, parking capacity that can be accommodated for cars of 14 vehicles and for motorcycles of 192 vehicles. Parking needs are 52 plots of parking for cars and 51 plots for motorcycles.